SHANK3 Antibody Validation: Differential Performance in Western Blotting, Immunocyto- and Immunohistochemistry - Lutz, Anne-Kathrin; Bauer, Helen Friedericke; Ioannidis, Valentin; Schön, Michael; Boeckers, Tobias M. (Frontiers in Synaptic Neuroscience, 2022)
SHANK3 is a scaffolding protein implicated in autism spectrum disorders (ASD). Its function at excitatory glutamatergic synapses has been studied for the last two decades, however, tissue-specific expression patterns as well as its subcellular localization need to be studied in further detail. Especially the close sequence homology of SHANK3 to its protein family members SHANK2 and SHANK1 raises the emerging need for specific antibodies that are validated for the desired methodology. With this study, we aim to validate a set of commercial as well as homemade SHANK3 antibodies in Western Blotting, and synaptic immunocyto- and immunohistochemistry. We found that only a small subset of the antibodies included in this study meet the criteria of quality and specificity. Therefore, we aim to share our findings on SHANK3 antibody validation but also raise awareness of the necessity of antibody specificity testing in the field.